Experimental Research of Dynamic Instabilities in the Presence of Coiled Wire Inserts on Two-Phase Flow - Gokhan Omeroglu; Omer Comakli; Sendogan Karagoz; Bayram Sahin (The Scientific World Journal)
The aim of this study is to experimentally investigate the effect of the coiled wire insertions on dynamic instabilities and to compare the results with the smooth tube for forced convection boiling. The experiments were conducted in a circular tube, and water was used as the working fluid. Two different pitch ratios (H/D=2.77 and 5.55) of coiled wire with circular cross-sections were utilised. The constant heat flux boundary condition was applied to the outer side of the test tube, and the constant exit restriction was used at the tube outlet. The mass flow rate changed from 110 to 20 g/s in order to obtain a detailed idea about the density wave and pressure drop oscillations, and the range of the inlet temperature was 15–35°C. The changes in pressure drop, inlet temperature, amplitude, and the period with mass flow rate are presented. For each configuration, it is seen that density wave and pressure drop oscillations occur at all inlet temperatures. Analyses show that the decrease in the mass flow rate and inlet temperature causes the amplitude and the period of the density wave and the pressure drop oscillations to decrease separately.